Correlation Between Destructive And None-Destructive Tests on the Mechanical Properties of Different Cement Mortar Mixtures Incorporated Polyethylene Terephthalate Fibers. - Alshkane, Younis M.; Rafiq, Serwan Kh.; Boiny, Hemn U. (Sulaimani Journal for Engineering Sciences, 2017)
Non-destructive tests have been widely used in engineering purposes especially in civil engineering. Yet it is not properly used to predict the mechanical properties of different cement mortar mixtures reinforced with plastic fibers (PET) made from waste plastic bottles. In this study, the pulse velocity was used to predict the mechanical properties of cement mortar mixtures reinforced with and without plastic fibers made from waste plastic fibers. The Pulse velocity was computed from samples of different cement mortar mixtures with different ratio of cement/sand. Then the desired mechanical properties of mortar samples were calculated from the laboratory tests. Then, the Pulse velocity results were correlated with the destructive test results using simple regression analysis. The results showed that the mechanical properties (Uniaxial Compressive Strength, Modulus of Elasticity, and Tensile strength) can be predicted from the correlation equations proposed in this study.
Keywords: Non-Destructive; Mechanical Properties; cement mortar; plastic fibers (PET)